2017
DOI: 10.1002/asi.23835
|View full text |Cite
|
Sign up to set email alerts
|

Implicit opinion analysis: Extraction and polarity labelling

Abstract: Opinion words are crucial information for sentiment analysis. In some text, however, opinion words are absent or highly ambiguous. The resulting implicit opinions are more difficult to extract and label than explicit ones. In this paper, cutting-edge machine-learning approachesdeep neural network and word-embedding -are adopted for implicit opinion mining at the snippet and clause levels. Hotel reviews written in Chinese are collected and annotated as the experimental data set. Results show the convolutional n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…B and A are the biases of hidden layer D and input layer x, respectively. Due to the limited ability of a single-layer autoencoder to extract signal features, classifiers such as SVM and SoftMax are generally added to the autoencoder [14].…”
Section: 13mentioning
confidence: 99%
“…B and A are the biases of hidden layer D and input layer x, respectively. Due to the limited ability of a single-layer autoencoder to extract signal features, classifiers such as SVM and SoftMax are generally added to the autoencoder [14].…”
Section: 13mentioning
confidence: 99%
“…In later work, Deng and Wiebe [27] detected implicitly expressed opinions by implicature inference over explicit sentiment expressions related to events affecting entities. In Chinese, Huang et al [28] annotated a corpus of hotel review snippets and clauses for positive and negative polarity. Recently, the SMP2019-ECISA (https://www.biendata.xyz/competition/smpecisa2019/ (accessed on 7 September 2021)) shared task for Chinese implicit sentiment in social media and car product and tourism forum posts based on Liao et al [7] has spurred new research in implicit polarity modeling.…”
Section: Implicit Sentimentmentioning
confidence: 99%
“…Studies have found that multi-feature classifiers perform better than single-feature one [9], and hybrid methods perform better than single one [9,24]. Recently, deep learning methods such as convolutional neural network and word-embedding outperformed traditional classification algorithm in the extraction of opinion words [25] and protein–protein interactions [26]. However, the major limitation of supervised method is the cost of data annotation.…”
Section: Literature Reviewmentioning
confidence: 99%